Fuqaha dan Kaderisasi: Histori, Kini dan Prospektif (Jejak Langkah Fuqaha dan Urgensi Kaderisasi Serta Prospek Fuqaha di Era Modern) - Nurhasmi N; Muhammad Shuhufi; Misbahuddin M (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Fuqaha have played a highly strategic historical role as the heirs of the Prophet in formulating Islamic law and guiding the Muslim community. Their trajectory, from the time of the Prophet Muhammad, through the period of the Rightly Guided Caliphs, to the formation of the classical schools of fiqh, demonstrates the importance of cadre formation in maintaining the continuity of the Islamic intellectual tradition. However, the dynamics of the modern era present new challenges distinct from the classical period, such as issues of medical bioethics, the development of Islamic fintech, gender justice, environmental crises, and the rights of persons with disabilities. These challenges require the formation of fuqaha who are not only grounded in textual sources but also oriented toward the objectives of Islamic law and contemporary fiqh methodologies. This article argues that the urgency of cadre formation of fuqaha in the modern era lies in the ability to produce a generation of scholars capable of integrating the classical fiqh tradition with modern interdisciplinary approaches. The prospect is the emergence of fuqaha who are responsive, visionary, and solution oriented, enabling Islamic fiqh to remain a relevant moral and legal guide for global society.